Uma experiência de contação de história na creche - Casagrande, Victor Hugo [UNESP]; Souza, Renata Junqueira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the world we live in our contemporary society we have lost the habit of reading. And TV has occupied this space, interaction time with friends and online entertainment, few those who experience their days reading good books. A survey in 2012 by the Pro-Book Institute shows that only 24% of the population have the habit of reading. For this picture to change, the reading should start for babies from pregnancy, ie the child in the belly and someone, like her mother reading to her. We know this is a difficult mother do because there may be cases of adult or have the habit of reading. So one should always encourage reading from drinking. Thinking about it, the Study Centre in Reading and Children's and Youth Literature "Maria Coelho Silva Betty" (CELLIJ) of the Universidade Estadual Paulista (UNESP), set up a project with fellows of the institution to take this reading to small of a nursery of the municipality . This text aims to present the storytelling of the book "Chicken which created a mouse," Ana Maria Machado. Methodologically, there was after the selection of the story-telling technique of choice in the case, storytelling with cash; preparation of the necessary resources and testing with the narrative study. As a result it was observed that, although the technique is very efficient, with smaller classes we can choose another way to tell. However, with larger classes, and in some ways even with the smallest, was involved with the story and participation of children, allowing them experience a moment of fantasy and love.

No mundo em que vivemos na nossa sociedade contemporânea tem se perdido o hábito de ler. E a TV tem ocupado esse espaço , tempo de interação com os amigos e diversões online, são poucos aqueles que vivenciam seus dias lendo bons livros. Uma pesquisa feita em 2012 pelo Instituto Pró- Livro mostra que apenas 24% da população têm o hábito de ler. Para que este quadro se modifique, a leitura deve começar para os bebes desde a gestação, ou seja, a criança na barriga e alguém, como a mãe lendo para ela. Sabemos que essa é uma tarefa difícil da mãe fazer, pois podem ocorrer casos de nem o adulto ter o hábito de ler. Por isso deve-se sempre incentivar a leitura desde bebe. Pensando nisso, o Centro de Estudos em Leitura e Literatura Infantil e Juvenil “Maria Betty Coelho Silva” (CELLIJ) da Universidade Estadual Paulista (UNESP), montaram um projeto com os bolsistas da instituição de levar essa leitura aos pequenos de uma creche do município. Este texto tem como objetivo apresentar a contação do livro “A galinha que criava um ratinho”, de Ana Maria Machado. Metodologicamente, houve após a seleção da história, escolha da técnica de contação, no caso, contação com caixa; preparação dos recursos necessários e ensaios com estudo da narrativa. Como resultados foi possível observar que, embora a técnica seja muito eficiente, com as turmas menores podemos optar por outra forma de contar. No entanto, com as turmas maiores, e de certo modo até com as menores, houve envolvimento com a história e participação das crianças, permitindo que elas vivenciassem um momento de fantasia e amor.
Keywords: Children's literature; Storytelling; Education; Literatura infantil; Contação de histórias; Educação